Новая разновидность Peridinium gatunense Nygaard f. kinnereta Krachmalny (Dinophyta) из озера Киннерет (Израиль) - Крахмальный, А.Ф.; Вассер, С.П.; Нево, Э.; Капитанчук, Л.М. (Альгология, 2014)
Представлено діагноз і опис нової форми Peridinium gatunense Nygaard f. kinneretа Krachmalny f. nov. із оз. Кіннерет. Від типової форми вона відрізняється будовою і розташуванням апікальних пластин і швів між ними (1’ – асиметрична, велика, її верхня частина зміщена в ліву сторону тіла; 3’ – клиновидна, витягнута; 4’ – майже прямокутна, її довжина більш як в два рази перевищує ширину; шви між 4’ і 7’’, 4’ и 1’ пластинами утворюють пряму лінію; шов між 1’ і 2’ пластинами значно меньший, ніж між 1’ і 4’, тому форма пластини 1’ наближається до трикутної). Зроблено порівняння P. gatunense f. kinneret зі зразками з інших місцезростань виду (прісні водойми Північної, Центральної, Південної Америки, Центральної Африки, Європи, Тасманії). Diagnosis and description of the new variety of Peridinium gatunense var. kinnereta Krachmalny var. nov. from the lake Kinneret (Israel) are given. This variety differs from the type one by the morphology and position of the apical plates and sutures between them (1’ – asymmetrical, large, its upper part is shifted to the left side of the body; 3’ – wedge, elongated; 4’ – almost rectangular, its length more than twice exceeds the width; sutures between 4’ and 7’’, 4’ and 1’ plates form an almost straight line; suture between 1’ and 2’ is considerably less than between1’ and 4’ plates, consequently the shape of the plate 1' is close to triangular). Comparison between P. gatunense var. kinnereta and the samples from the other regions where this species is recorded (fresh reservouars of the North, Central and South America, Central Africa, Europe and Tasmania) was carried out.